Exploring design discourses and liminality as features of professional learning in an elementary makerspace. Issue 5 (21st March 2022) - Becker, Sandra; Jacobsen, Michele
Abstract : Purpose: Using Johansson-Sköldberg et al. 's (2013 ) descriptions of design discourses, this study aims to analyze teacher interviews, research notes and teacher and student artifacts to determine if engagement in design practices led to changes in the teacher's thinking. Design/methodology/approach: This article presents results from a year-long study that explored how a teacher enacted design discourses to engage in curriculum learning within an elementary school makerspace. The design-based study involved a collaborative partnership where a teacher and researcher co-designed, co-enacted and co-reflected on three cycles of making featuring curriculum studies in science, mathematics and social studies. Findings: The authors determined that engagement in all four design discourses led to transformative changes in the teacher's thinking about herself as a teacher and her students as learners. The evidence suggests the school makerspace can serve as a liminal design space for professional learning, given that implicit in the makerspace is the embodiment of design practices such as problem finding, iteration and reflection. Research limitations/implications: Engaging in design discourses in the makerspace can lead teachers to question the frames they hold about teaching and learning. However, teachers need ongoing support in developing discipline knowledge and prioritizing the time required for designing, iterating and reflecting on learning in the makerspace. Practical implications: The makerspace provides a liminal space for teachers' professional learning in that implicit in the makerspace is the embodiment of design practices such as problem finding, iteration and reflection. Originality/value: This study is unique, in that it places the importance of teacher learning in the elementary school makerspace on equal footing with student learning, thereby creating a culture of inquiry for all.